The disruptive strategy of Orange in the payment and banking industry in Africa and its knowledge links with its strategy in the European market - Essence Ambe Chick; Pierre Vialle; Jason Whalley (International Telecommunications Society (ITS), 2023)
This study examines the trajectory of Orange's payment and banking services in Africa and the role of experiential knowledge, resources, and capabilities accumulated in Africa and Europe. The study is carried out through a chronological analysis of annual reports from 2008 to 2021, identifying events in financial innovations. Results show that, from the categorization of Orange's mobile financial and banking services within this study scope, it started from simple and secured mobile payments and expanded to advanced financial services, such as credits and savings to meet the growing demand of its markets. Also, there was a strong synergy between accumulated experiences in Africa and Europe, enabling rapid innovation development at minimal costs. Finally, while the Orange money innovation was disruptive in Africa, as it responded to the needs of the huge lowend market in Africa, which has been deprived of banking service, this was not the case with its transfer to Europe, which is an advanced market with numerous established players.
Keywords: 330; Orange; Africa; disruption; mobile payment; mobile telecommunications; banking